KADAR CTX PEREMPUAN OSTEOPOROSIS LEBIH TINGGI DARIPADA PEREMPUAN NORMAL DAN OSTEOPENIA - Ira Puspitawati; Windarwati Windarwati; Usi Sukorini; Erlina Erlina; Pratiwi Herowati; Arlan Prabowo; Riswan Hadi Kusuma (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Regarding to the ageing population in most countries, degenerative and metabolism diseases included osteoporosis are becoming increasingly and need special attention in all country especially in the developing country such as Indonesia. Current WHO recommendation of using a gold standard for establishing osteoporosis is by Dual X-Ray Absorptiometry (DEXA), but it is expensive and not yet widely available. There are some alternatives of biochemical markers that can reflect the bone turn over. One of them is Cterminal cross-linking telopeptide of type I collagen (CTX) or betacrosslabs, a marker of bone resorbtion. There are still limited studies on correlation of CTX and osteoporosis in peri menopausal and post menopausal women. The aim of this study is to know whether there are any differences of CTX level among peri menopausal and post menopausal women with different bone density. This research was a cross sectional study and aimed to know whether there is any correlation between CTX level and Bone Mineral Density Score measured with DEXA. The study was conducted in June-August 2010. The included subjects were women with age more than 45 years old, without apparent history of neoplasm, impaired renal function, bone metabolic diseases, and not currently pregnant. CTX level were measured using immunochemiluminescent. Their data were analysed using One Way ANOVA. This study showed that there are differences of CTX levels among women with osteoporosis, osteopenia, and normal (0.633±0.25 ng/mL vs 0.514±0.21 ng/mL vs 0.406±0.21 ng/mL p=0.02). Osteoporosis women have higher CTX level compared to Osteopenia and Normal women.